Pulse frequency effect on the NiTi plasmas characteristics and thin film properties and fabrication of NiTi micro-comb structures. (2022) - Jithin, M.A.; Sidhila, P.S.; Udayashankar, N.K.
Abstract: Nickel-titanium (NiTi) is a thermal shape memory alloy (SMA) widely used in the actuator domain in miniaturized systems. With a titanium nitride (TiN) capping layer, NiTi exhibits better mechanical properties and enhances biocompatibility in biomedical applications. In addition, TiN can be efficiently heated to a higher temperature than induce the phase transformation in NiTi MEMS structures. This could be easily achieved by fabricating a TiN heater pattern over or alongside the NiTi MEMS structures. The subject of this work is the NiTi thin films deposited utilizing the pulsed DC magnetron sputter (PDCMS) deposition process at various pulse frequencies (50–350 kHz). The TiN capping layer was also grown on the Si/NiTi stack by the same process. The NiTi micro-comb and TiN micro-heater MEMS structures were fabricated using bulk laser micromachining. Freestanding MEMS structures of NiTi and TiN thin films were realized by etching the bottom silicon with an etch rate of 600 nm/Sec using chemical wet etch by tetramethylammonium hydroxide TMAH.